2022
DOI: 10.3390/toxics10030118
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for Detecting Microplastics Based on Fluorescence Lifetime Imaging Technology (FLIM)

Abstract: With the increasing use and release of plastic products, microplastics have rapidly accumulated in ecological environments. When microplastics enter the food chain, they cause serious harm to organisms and humans. Microplastics pollution has become a growing concern worldwide; however, there is still no standardized method for rapidly and accurately detecting microplastics. In this work, we used fluorescence lifetime imaging technology to detect four kinds of Nile red-stained and unstained microplastics, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Prior reports of monitoring polymerization progress using autofluorescence in examples of hydrogels, dendrimers, polymeric micelles, and clusters describe specific functional groups (e.g., carbonyls) as causes of autofluorescence, and do not appear to contain all-hydrocarbon polymer examples that would be relevant here. [42,43] Interestingly, isolated solid microplastics, including the hydrocarbon polyethylene, have been shown to be autofluorescent, but no examples exist of harnessing autofluorescence of these materials for reaction monitoring; [44][45][46][47][48] there are also no examples which suggest these polymers are autofluorescent in solutions, in gels, or as oligomers, conditions relevant to this real-time reaction monitoring system.…”
Section: Resultsmentioning
confidence: 99%
“…Prior reports of monitoring polymerization progress using autofluorescence in examples of hydrogels, dendrimers, polymeric micelles, and clusters describe specific functional groups (e.g., carbonyls) as causes of autofluorescence, and do not appear to contain all-hydrocarbon polymer examples that would be relevant here. [42,43] Interestingly, isolated solid microplastics, including the hydrocarbon polyethylene, have been shown to be autofluorescent, but no examples exist of harnessing autofluorescence of these materials for reaction monitoring; [44][45][46][47][48] there are also no examples which suggest these polymers are autofluorescent in solutions, in gels, or as oligomers, conditions relevant to this real-time reaction monitoring system.…”
Section: Resultsmentioning
confidence: 99%
“…The properties of other techniques that have been used in the analysis of plastic debris to a lesser degree, including gel permeation chromatography and liquid chromatography, are presented in Table 2. • Time-consuming (Käppler et al, 2016;Cabernard et al, 2018;Xu et al, 2019;Cerasa et al, 2021;Zhou et al, 2022) Gas Chromatography-Mass Spectrometry (GC-…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Fluorescence lifetime imaging microscopy (FLIM) uses a femtosecond pulsed laser with a high repetition rate to excite fluorescence from a sample. Such methodology offers strong specificity, high sensitivity, and the ability to perform quantitative measurements, mainly because the fluorescence probe concentration, excitation light intensity, photobleaching, or any other factors, do not affect the measurement of fluorescence lifetime [101] . For this reason, this methodology has been recently applied to microplastics research.…”
Section: Fluorescence Lifetime Imaging Technology (Flim) To Track The...mentioning
confidence: 99%
“…Only very recently, a study confirmed the success of this methodology in detecting and analyzing microplastics in the presence of matrix interferents and even complex environmental matrixes (such as the presence of biological macromolecules and inorganic material). Zhou et al [101] studied the spectra of different microplastics (ABS, PET, PVC, PLA), using the continuous excitation lines of a pulsed laser to determine the detection range of microplastics, and verified their applicability in the presence of single and complex matrixes (e.g., presence of silica, chitin, decabromodyphenyl ethane, surface sediments from a lake). This methodology was used to detect stained and unstained microplastics, and the unique phasor fingerprints of different microplastics were obtained by phasor analysis (a visual fluorescence lifetime analytical method that visualizes fluorescence decay data without fitting).…”
Section: Fluorescence Lifetime Imaging Technology (Flim) To Track The...mentioning
confidence: 99%